Design and Comparison of Reconfigurable Perfectly- Matched Bandstop Filters - Ahmad, B. H.; Zahari , M. K.; Wong, Peng Wen (Buldanshahr : IJECSE, 2013)
Abstract- This paper discusses two new designs of reconfigurable perfectly-matched bandstop filter which is based on L-shape and ring resonator. The perfectly-matched bandstop filters can be reconfigured between allpass and bandstop response using PIN diodes as switching elements. The operating center frequency of these filters is at 1 GHz. The discussions of the conceptual perfectly-matched bandstop filters are included in this paper. The filters have been simulated for analysis where the effect of microstrip line and FR4 substrate has been taken into account. It is then further fabricated and measured for verification. The filters will then be compared in terms of s-parameter and size. Result shows good agreement between simulation and measurement.